HPLC identification of Rutin (3, 3′, 4′, 5, 7-pentahydroxyflavone-3-rhamnoglucoside) from Costus pictus leaves extract and evaluation of its antioxidant activity (Asian Journal of Medical and Biological Research, 2020)
Plants synthesise many secondary metabolites which are of great medicinal value. Costus pictus also known as Insulin plant is considered as valuable medicinal plant in preparation of many commercial pharmaceutical products. The aim of the present study is to identify one such secondary metabolite flavonoid (Rutin) in the leaves of Costus pictus by HPLC method and also to evaluate the antioxidant potential of Ethyl acetate extract of Costus using DPPH and NO scavenging assay. The Extracted materi al was identified as Rutin by comparing with Standard Rutin. Both the samples showed similar retention time of 2.8 minutes. The extract showed maximum DPPH free radical scavenging activity with increase in concentration and IC50 of Nitric acid scavenging activity was found to be more for the Extract than the standard ascorbic acid and Rutin. From this study it is concluded that Costus pictus leaves extract can be used as natural food supplement.Asian J. Med. Biol. Res. June 2020, 6(2): 334-339